Realizing simultaneous improvements in mechanical strength, flame retardancy and smoke suppression of ABS nanocomposites from multifunctional graphene. (15th November 2019) - Huang, Guobo; Huo, Siqi; Xu, Xiaodong; Chen, Wei; Jin, Yanxian; Li, Rongrong; Song, Pingan; Wang, Hao
Abstract: Acrylonitrile-butadiene-styrene (ABS), as one of the most widely used engineering plastics, suffers from the problem of serious flammability and low mechanical strength. To address such an intractable challenge, herein, we report the design of a graphene-based multifunctional additive (Sb-Mo/Br-rGO) via the bromination followed by precipitating antimony molybdenum. The surface functionalization enables Sb-Mo/Br-rGO to homogeneously disperse within the ABS matrix through facile melt-blending. The incorporation of 5 wt% Sb-Mo/Br-rGO leads to a 31% increase in tensile strength and 73% increase in elastic modulus relative to the ABS bulk. In addition to significant enhancement in thermal stability, the inclusion of 5 wt% Sb-Mo/Br-rGO significantly delays the time to ignition of ABS by 12 s, and noticeably reduces the peak heat release rate (PHRR) and total smoke production (TSP) by 45% and 54%, respectively. Such improved performance portfolio is primarily because the mechanical reinforcing and thermal barrier effect of graphene nanosheets, the flame retardant effect of bromine/antimony, and the smoke suppression action of antimony molybdenum. This work provides an innovative methodology for the design of multifunctional additives to create high-performance polymeric materials with high strength and low flammability, thus contributing to improving the quality of life. Graphical abstract: Image 1 Highlights: A novel multifunctional graphene-based flame retardant, Sb-Mo/Br-rGO, has been fabricated. The addition of 5 wt% of SbMo-BrG increases tensile strength of ABS from 52.2 to 68.4 MPa. The addition of Sb-Mo/Br-rGO significantly extends the time to ignition of ABS. The addition of 5 wt% Sb-Mo/Br-rGO respectively reduces the PHRR and total smoke production by 45% and 54%.